Libraries are not Trading Houses! - Aydın İleri (Türk Kütüphaneciliği)
This is the reviewed version of the assertion shared on 29 November 2016 at Kutup-L professional discussion list and prepared by school libraries association in relation to the collecting societies’ asking for Money for preventing writer’s rights as much as the the number of books lent.